Exploring Students’ Learning Styles in English Language Learning: Implications for Differentiated Instruction Strategies - Rohmah, Dine Fitriana; Fitriah, Fitriah; Marharini, Swasti (Universitas Pahlawan Tuanku Tambusai, 2025)
Learning styles play an important role in shaping how students process and internalize language input. Information about students’ learning styles enables teachers to select appropriate approaches that address and accommodate their needs. This study investigates the preferred learning styles of junior high school students in English language learning and examines the implications for differentiated instructions. Using a quantitative descriptive design, data were collected from 45 eighth-grade students through a standardized learning style questionnaire adapted from Nisa’ul Kumalasari. The results reveal that seven categories of learning style are identified, namely visual learning, tactile learning, auditory learning, group learning, individual learning, reading learning, and kinesthetic learning. From the seven categories, auditory learning and tactile styles emerged as the two most dominants. These findings indicate that students learn more effectively through listening and collaborative interactions. This highlights the need for teachers to implement multimodal instructional strategies that integrate auditory, visual, and kinesthetic elements to accommodate diverse student needs and enhance learning engagement.